Revamping crop insurance in the context of climate change in Oridsha - Swain, Mamata (Man & Development)
Climate change has emerged as a major there to Indian agriculture. There is a great need for crop insurance to proved economic support to farmers and stabilise there farm income in the even of crop failure. This paper assesses the performances of national agricultural insurance Insurance scheme (NAIS) (area-based crop yield insurance) and the pilot weather based crop Insurance scheme (WBCIS) (area-based rainfall insurance) implemented in the state of Odisha, the climate change potshot of India -Reproduced
Keywords: Climate change, Agricultural risk, Adaptation, Crop insurance, Odisha, India